Factors of financial stability of Ukrainian banks: impact and trends - Doroshenko, N.; Shynkarenko, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2024)
The financial stability of banks is critically important for ensuring the stability of the financial system and economic development. This study analyzes the influence of various factors on the financial stability of banks, such as liquidity, profitability, monetary policy, political situation, technological development and human factors. The purpose of this study is to identify and analyze factors that affect the financial stability of banks using a structural approach. Tasks include studying the influence of indicators of banking activity on their financial stability. The study identifies key factors such as capital levels, asset quality, liquidity, yield, profitability and monetary policy and analyzes their interactions. The study based on data from Ukraine made the following conclusions: Liquidity is a key aspect of financial stability, determining the bank's ability to meet its financial obligations on time. Profitability and profitability play an important role in ensuring financial stability, allowing banks to cover possible losses and perform their functions effectively. The monetary policy of the central bank significantly affects the conditions of operation of banks, determining interest rates and the amount of money in the system. The political situation in the country can also have a great impact on the financial stability of banks due to the effect of instability and risks associated with changes in legislation and regulation. Technological development plays an increasingly important role in the financial sector, contributing to the efficiency and competitiveness of banks. However, the growing cyber threat requires banks to focus on cyber security and innovation. Finally, the human factor, such as the qualifications and work ethics of employees, plays a key role in ensuring effective risk management and financial stability. All these factors are of great importance for the financial stability of banks, and their effective management is essential to ensure the stability of the financial system as a whole. The results of this study can serve as a basis for developing risk management strategies and improving the financial stability of banks in modern economic conditions. The findings show that successful management of risks and the impact of these factors is key to ensuring the stability of the financial system as a whole.